Flora Lexicon in The Paribahasa Banjar of Southern Kalimantan In The Perspective of Ecolinguistics As an Indonesian Language Teaching Material Indonesian Language Teaching Materials in Elementary School - Kasmilawati, Isna; Agustina, Lili; Suciati, Nana (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Paribahasa is an expression containing comparisons, parables, life advice or rules of behavior. Paribahasa is one of the Banjar oral literature which is full of advice. Paribahasa Banjar is also one of the Indonesian language materials in elementary school which is not only introduced but also understood by students as the life of Banjar culture. This research aims to describe the flora lexicon in Banjar speech in South Kalimantan. Banjar paribahasa was chosen as the source of this research because Banjar paribahasa is one of the traditions of the Banjar people which is full of advice on the life of its people with the surrounding natural environment. The type of research used is descriptive qualitative because this research will provide information about the use of flora lexicon in Banjar paribahasa of South Kalimantan. The data of this research is Banjar lexicon that uses plant elements, types of plants, and things related to plants. The data source used in this research is a collection of Banjar sayings that have been recorded. The results show that there are 14 Banjar sayings that have plant elements such as; a) kancur, b) jariangau, c) asam, d) janar, e) bamban, f) lumbuk, g) tarap, h) hanau, i) banana, j) nyiur, k) kaminting, l) bungur, m) paring, and n) waluh. This shows that plant elements, plant species, and things related to plants are considered important by the Banjar people.